Effect of macrodiversity on average-error probabilities in a Rician fading channel with correlated lognormal shadowing. - Jingjun Zhang (IEEE Transactions on communications)
The effect of correlated lognormal shadowing on the average probability of error performance of narrow-band mobile communication systems with micro- and macrodiversity reception in a Rician fading channel is studied by considering a constant correlation model for the shadowed signals at the base stations. The performance degradation due to correlated shadowing is illustrated by considering both coherent and differentially coherent binary phase-shift keying schemes. Numerical results presented show that when the base stations in a cellular system are very closely spaced, the effect of correlated shadowing on system performance cannot be ignored